Climate change and conflict in West Africa - Raji, Rafiq (2020)
Climate change is the long-term modification of the Earth’s climate resulting from atmospheric changes and interactions among the atmosphere and other geological, chemical, biological, and spatial factors within the Earth’s powerful energy system. Climate scientists who collect and analyze information about our planet and climate on a global scale report an accelerating global rise in average temperature from the late 19th century to the present, nearing one degree Celsius. Leading scientists view this temperature change, accompanied by sea ice losses, sea level rises, longer, more intense heat waves and other increases in extreme weather events, as robust evidence of climate change.